Constructing the Meaning of Childhood Parenting Wounds on Self-Management Quality - Suprayogi, Roi Anjas; Bintari, Dewi Sawitra; Yuzak, Nurul; Sugiarti, Lucia Rini; Suhariadi, Fendy (Al-Qalam Institue, 2025)
This study aims to explore how unresolved parenting wounds influence self-management in adulthood, particularly in the areas of emotional regulation, interpersonal relationships, financial independence, and career development. The background of this research highlights the significant role of early parental relationships in shaping psychological and behavioral patterns that persist into adulthood, often manifesting as challenges in managing emotions, relationships, and responsibilities. A qualitative research design was employed, using a case study approach to examine the experiences of a client undergoing hypnotherapy. Findings from the study revealed three key insights childhood parenting patterns marked by frequent verbal conflicts and emotional volatility, leading to emotional insecurity, persistent emotional responses such as sadness, anger, and helplessness that suggest unresolved trauma, and career and performance instability, largely influenced by emotional burnout and a lack of assertiveness. The study concludes with recommendations for future research to explore a broader and more diverse sample, including longitudinal studies that track the long-term effects of parenting wounds. Additionally, the integration of various therapeutic approaches such as cognitive-behavioral therapy could enhance the understanding of how best to address these challenges and improve self-management in adulthood.